Development and Validation of the Coping With Acculturative Stress in American Schools (CASAS-A) Scale on a Latino Adolescent Sample. (December 2014) - Castro-Olivo, Sara M.; Palardy, Gregory J.; Albeg, Loren; Williamson, Ariel A.
The psychometric properties of the Coping With Acculturative Stress in American Schools (CASAS-A) scale were examined using a sample of 148 Latino middle school students. CASAS-A is a self-report scale designed to identify students in need of culturally responsive social–emotional interventions due to having high levels of school-related acculturative stress. Confirmatory factor analysis (CFA), analyses of internal consistency, correlations with related measures, and group differences among Latino English Language Learners (ELLs) and non-ELLs were examined. The CFA results indicate that the data fit the hypothesized factor structure. The results also support adequate levels of reliability and validity. In addition, significant group differences were found between Latino ELLs and non-ELLs, with Latino ELLs reporting higher levels of acculturative stress in CASAS-A. Implications for future research, as well as recommendations for practitioners who implement culturally responsive interventions, are discussed.